Acoustic analysis of the speech of children with cochlear implants: A longitudinal study - Liker, Marko; Mildner, Vesna; Šindija, Branka (2007)
The aim of the study was to analyse the speech of the children with cochlear implants, and compare it with the speech of hearing controls. We focused on three categories of Croatian sounds: vowels (F1 and F2 frequencies), fricatives (noise frequencies of /s/ and /int/ ), and affricates (total duration and the pattern of stop-fricative components in /ts/ and /tint/ ). Eighteen implanted children, aged between 9 ; 5 and 15 ; 2 years participated in the study. All had been profoundly hearing impaired before implantation. Three recordings per child were made over a 20-month period. The hearing controls were matched for age and sex. Implanted children had a smaller and fronted vowel space, their /s/ and /int/ noise frequencies overlapped, affricates were longer, with a high proportion of incorrect productions and substitutions. With time, there was a small but steady overall improvement in all categories. Early intervention (rehabilitation and implantation) are crucial for good speech acquisition. Projekt / tema: 130-0000000-0785 Izvorni jezik: ENG Current Contents: DA Citation Index: DA Ostale indexne publikacije: Index Medicus ; Linguistics and Language Behavior Abstracts ; Social Sciences Index ; Sociological Abstracts ; CSA Linguistics & Language Behaviour Abstracts ; EBSCO Online ; EMBASE/Excerpta Medica ; Family Index Database ; PsycINFO ; Research Alert ; SciSearch Kategorija: Znanstveni Znanstvena područja: Filologija Tiskani medij: da Upisao u CROSBI: Marko Liker (ahab-ff@bigfoot.com), 19. Lip. 2007. u 11:57 sati
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG